Declining Time‐Trend in Loneliness Levels Among Migrant Children in Urban China, 2006−2019: A Cross‐Temporal Meta‐Analysis of 40 Studies Published From 2006 to 2022 - Ge, Lin-Feng; Wu, Rui-Yao; Zhong, Bao-Liang (Depression and anxiety, 2024)
Loneliness has long been a significant psychosocial problem for migrant children in urban China. In recent years, social changes and enhancements in social welfare equity have lessened the disadvantages faced by these migrant children. The current study investigated the time‐trend of loneliness levels among migrant children from 2006 to 2019. A literature search was performed within major Chinese‐ and English‐language databases, and studies that reported the means and standard deviations of Children’s Loneliness Scale (CLS) scores among Chinese migrant children were included in this cross‐temporal meta‐analysis. Weighted linear regression was conducted to examine the trend of mean CLS scores over the survey year, and Cohen’s d value was calculated to assess the magnitude of change. In total, 40 cross‐sectional studies conducted between 2006 and 2019 (published by 2022), consisting of 47 cohorts of migrant children and a total sample size of 17,090, were included. Overall, there was a significant downward trend between the survey year and mean CLS score (unstandardized coefficient [ β ] = −0.342, P < 0.001), and Cohen’s d value of this decline from 2006 to 2019 was 0.411. Similar declining time‐trends were also observed among subgroups when broken down by sex, school type, and geographic regions ( β = −0.182 to −0.589, P < 0.001, d = 0.222–0.719). The loneliness levels of migrant children in urban China decreased from 2006 to 2019. Nevertheless, sustained measures and inclusive policies are still needed to mitigate the loneliness levels of Chinese migrant children.